Angelica sinensis reduced Aβ-induced memory impairment in rats. (20th April 2016) - Duan, Ming-Hua; Wang, Li-Na; Jiang, Yan-Hong; Pei, Ying-Yuan; Guan, Dong-Dong; Qiu, Zhi-Dong
Abstract: Background : Studies have shown that Angelica sinensis (JiLin AoDong Medicine Industry Groups Co., Ltd., Jilin, China) root (AS) ameliorates various diseases, although its effects in Alzheimer's disease (AD) have not been elucidated. Purpose : The present study examined the effects of AS in a rat model of AD. Methods : Positional Aβ injections were administered to rats. The behavioral effects of AS administration were examined using the Morris water maze, and the molecular effects on gene and protein expression, and apoptosis, were determined. Results : AS reversed the social behavioral impairments observed in this rat model of Aβ-induced memory impairment. Western blot analysis also revealed lower hippocampal levels of Aβ and β-site amyloid precursor protein-cleaving enzyme. Terminal deoxynucleotidyl transferased UTP nick end labeling indicated that AS significantly inhibited apoptosis via effects on nuclear factor kappa B (NF-κB) signaling. Real-time PCR, enzyme-linked immunosorbent assay, and immunohistochemical staining indicated that AS effectively inhibited inflammation and upregulated expression of glial cell line-derived neurotrophic factor (GDNF) and brain-derived neurotrophic factor (BDNF) in the hippocampus of this rat AD model. Discussion : AS effectively rescued the symptoms of AD in a rat model by inhibiting inflammation, apoptosis, and NF-κB signaling pathway. Conclusion : These findings suggested that AS could provide a potential drug for the treatment of AD.